The slim mute crickets, Euscyrtinae (Orthoptera: Grylloidea; Gryllidae; Euscyrtinae) of Taiwan with three new species and lectotype designations of three of Shiraki’s species - Yang, Jeng-Tze; Yang, Ching-Shan (Zootaxa, 2012)
Three genera and five species of Taiwanese Euscyrtinae possess developed tegmina but produce no sound at all. In thispaper, we report on 10 species in 3 genera including 3 new species, i.e., Beybienkoana splendida n. sp., B. luteola n. sp.and B. gregaria n. sp. Lectotypes of three Shiraki’s species, i.e., Euscyrtus japonicus Shiraki 1930, Beybienkoana formo-sana (Shiraki, 1930) and Beybienkoana karnyi (Shiraki, 1930) are designated. The types are deposited in the collection ofDepartment of Entomology, National Taiwan University. In addition, Euscyrtus japonicus Shiraki, 1930 and Patiscus ma-layanus Chopard, 1969, are recorded are recorded from Taiwan for the first time. The morphology, including the ultra finestructure of metanotal gland, and ecology, including habitats and host plants, are applied in the taxonomy of this subfamily.The structure of the metanotal gland is described in detail using the Scanning Electronic Microscope. In this paper sometaxonomic characters are used for the first time in this group. The definition of Euscyrtinae emended with the structure ofmetanotal glands presented as new character for subfamily definition. A key to genera and to species of Euscyrtinae from Taiwan provided in this paper as well.